PENGARUH KUALITAS INTERAKSI DAN LINGKUNGAN FISIK TERHADAP KEPERCAYAAN DAN LOYALITAS MELALUI PERSEPSI KEUNGGULAN KINERJA - Asep Hermawan (Media Riset Bisnis & Manajemen, 2006)
The purpose of this study is to examine the effect of interaction quality and physical atmosphere towards loyalty mediated by perceived performance excellent and trust in a high contact service context, namely dentist service environment. Results found the supports of the mediating role of perceived perfomiance excellence and trust for interaction quality. Managerial implications and recommendations for future study are provided.